Drawing Picture Media in Teaching English Speaking: Learning Opportunity and Students’ Perception - Hamzarwadi; Husnu, Muhammad; Mardiyah, Nafis Ainul (English Education:Journal of English Teaching and Research, 2022)
The purpose of this study was to clarify and investigate the effect of Drawing Picture Media on improving the students’ speaking skills and their responses to the use of picture media in Indonesian EFL classrooms. In this case, the researcher used quantitative and qualitative research methods. Quantitatively, the data was collected by using a pre-experimental design, with a treatment to the One Group Pretest-Posttest group. Before the researcher gave treatment, the average score of students was 11.13, then increased to 15.13 after the treatment. Therefore, learning using the Drawing Picture Media method significantly improves students' speaking skills. The results of data analysis using observations and questionnaires showed that most of the students (83%) responded very well to the drawing picture media that was used in learning English in the classroom. From these results, the researcher can conclude that students' perceptions of the learning media were excellent.